Institutional regime shift in intellectual property rights and innovation strategies of firms in China - HUANG, Kenneth G. L. (Institutional Knowledge at Singapore Management University, 2017)
This study develops a novel conceptual framework to understand the differential impact of formal institutional regime shift in intellectual property rights on the innovation and patenting strategies of Chinese and Western ﬁrms operating in China. We argue that to the extent that Chinese ﬁrms have been deeply embedded in China’s informal institutions,they are less responsive to formal institutional changes than Western ﬁrms operating in China. Using the major China patent law reform of 2001 as an exogenous event, we ﬁnd results consistent with our key arguments: With the strengthening of the previously weak (utility model) patent protection, Chinese ﬁrms are less likely to apply for such patents to safeguard their innovations than Western ﬁrms. However, this diﬀerence becomes less pronounced in regions with higher quality intellectual property rights and legal institutions that foster research and development and innovation, and when Western ﬁrms gain longer operational experience in China.This study advances our understanding of the intricate interaction between formal and informal institutions and speciﬁcally how "stickiness" may arise in their substitutive relationship because of the embeddedness of ﬁrms in informal institutional environments.It also provides important implications for policy and innovation strategies for policy makers and ﬁrms in emerging economies.